1993
DOI: 10.1007/bf00712988
|View full text |Cite
|
Sign up to set email alerts
|

A 28-kDa cerebral neuropeptide fromManduca sexta: Relationship to the insect prothoracicotropic hormone

Abstract: 1. A 28-kDa peptide from the brain of the tobacco hornworm, Manduca sexta, was purified via HPLC. The peptide copurified with the insect neurohormone, prothoracicotropic hormone (PTTH), through two HPLC columns. 2. Immunocytochemistry using polyclonal antibodies against the 28-kDa peptide revealed that the peptide was produced in the same protocerebral neurons that produce PTTH. Western blot analysis demonstrated that the 28-kDa peptide and big PTTH are different molecules. 3. A PTTH in vitro bioassay indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…PTTH itself may play this role (23,26) or other small peptides produced during the processing of the big PTTH precursor molecule (prepro-PTTH) might be involved (23,39). In Manduca sexta an additional 28-kDa peptide unrelated to big PTTH is also produced by the prothoracicotropes and packaged into neurosecretory vesicles, although its function is as yet unclear (40).…”
Section: Methodsmentioning
confidence: 99%
“…PTTH itself may play this role (23,26) or other small peptides produced during the processing of the big PTTH precursor molecule (prepro-PTTH) might be involved (23,39). In Manduca sexta an additional 28-kDa peptide unrelated to big PTTH is also produced by the prothoracicotropes and packaged into neurosecretory vesicles, although its function is as yet unclear (40).…”
Section: Methodsmentioning
confidence: 99%
“…An advantage of Manduca is that it has paired prothoracic glands which produce ecdysone at the same rate, which means that experimental manipulation can be conducted on one gland, with the other serving as a control [55]. Studies in Manduca found that PTTH was also synthesized in this species, but the peptide was produced in two different sizes; big PTTH and small PTTH [56,57]. Both of these peptides have been shown to stimulate Manduca prothoracic glands to produce ecdysone in vitro [58].…”
Section: The First Peptides Shown To Regulate Ecdysone Production Wermentioning
confidence: 99%